Poaching and hunting, conflicts and health: human dimensions of wildlife conservation in the Brazilian Cerrado - Roberta Montanheiro Paolino; Roberta Montanheiro Paolino; Caroline Testa José; Renata Carolina Fernandes-Santos; Renata Carolina Fernandes-Santos; Mariana Bueno Landis; Mariana Bueno Landis; Gabriela Medeiros de Pinho; Gabriela Medeiros de Pinho; Emília Patrícia Medici; Emília Patrícia Medici; Emília Patrícia Medici (Frontiers in Conservation Science, 2024)
IntroductionUnderstanding human-wildlife interactions is critical to overcoming the socio-environmental crises we face worldwide. Among these interactions, poaching and hunting, human-wildlife conflict, and transmission of zoonotic diseases are major causes of biodiversity loss and detrimental to human well-being. Therefore, this study aimed to analyze wildlife poaching, feral pig hunting, human-wildlife conflict, and health issues in a region of the Brazilian Cerrado, in the state of Mato Grosso do Sul. The study also focused on the lowland tapir (Tapirus terrestris), a poached species listed as vulnerable to extinction.MethodsFrom October 2016 to September 2017, we conducted face-to-face semi-structured interviews with 51 local people from nine stakeholder groups. Interview answers and additional information compiled during the study were evaluated using coding, narrative, and co-occurrence analyses.Results and discussionWe found that the main human-wildlife conflict in the region involves feral pigs, and hunting is practiced as a population control strategy. The lowland tapir is not considered a conflictual species, as it is beloved by most people. However, tapirs are still poached, although less so than in the past, mainly for cultural reasons. Culture was the main motivation behind wildlife poaching in general. We identified 28 species and five taxa currently poached in this Cerrado region, of which 11 are used for medical and aphrodisiac purposes. Historically, wildlife poaching was linked to poor livelihood conditions and lack of support from governmental institutions during the Agrarian Reform process, becoming a cultural habit over the years. Nevertheless, wildlife poaching is less frequent than in the past, and its main barriers are surveillance, poaching prohibition by landowners, and social norm. Therefore, promoting a change in the way people relate to nature, meeting socioeconomic needs, and increasing surveillance appear to be important conservation strategies. Although feral pig hunting may replace wildlife poaching, some hunters still poach wild species, especially peccaries. Hence, it is necessary to keep hunters under surveillance, raise awareness among them, and make them allies in conservation strategies. We found a worryingly low level of awareness about disease transmission risk through bushmeat manipulation and consumption, highlighting the importance of One Health approaches.